Faculty Senate, Agenda, September 18, 2008 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2008)
Valdosta State University. Faculty Senate, Agenda, September 18, 2008.
Faculty Senate, Agenda, September 18, 2008. 19 pages.
Keywords: Electronic records; Corporation reports; Valdosta State University. Faculty Senate; Committees